De l’utopie à la nostalgie en Algérie française - Thomas Dodman (Conserveries Mémorielles)
This article explores the moment when utopia and nostalgia crossed paths during the colonization of Algeria in the mid-nineteenth century. It analyses these two concepts as forms of practice, in colonization plans and the work of medical officers on the ground. Their encounter reveals a complex relation to time and space that unites these two seemingly opposed ideas as an antinomic form specific to modernity.